The Future Defense System for the Indonesian Nation State - Triswan Larosa (The Republic of Indonesia Defense University, 2017)
The curent global situation has encouraged inter-state rivalry to become increasingly violent, so that the survival of every nation-state is becoming increasingly vulnerable. Therefore, every nation state has a responsibility to develop its own defense system to deal with the physical and psychological threats. This paper discusses the challenges and concepts of future defense system for the Indonesia, with the framework of analysis is the security vortex. The concept of the future defense system for the nation state of Indonesia is concentric defense, which consists of internal and external defense belt, by building three basic capabilities of the TNI to ensure national security, and to build global strategic partnership, which put Indonesia as an initial buffer of regional stability.